Acquisition of tenofovir-susceptible, emtricitabine-resistant HIV despite high adherence to daily pre-exposure prophylaxis: a case report. Issue 1 (January 2019) - Cohen, Stephanie E; Sachdev, Darpun; Lee, Sulggi A; Scheer, Susan; Bacon, Oliver; Chen, Miao-Jung; Okochi, Hideaki; Anderson, Peter L; Kearney, Mary F; Coffey, Susa; Scott, Hyman; Grant, Robert M; et al.
Summary: Background: Pre-exposure prophylaxis (PrEP) with emtricitabine and tenofovir disoproxil fumarate is highly protective against HIV infection. We report a case of tenofovir-susceptible, emtricitabine-resistant HIV acquisition despite high adherence to daily PrEP. Methods: Adherence to PrEP was assessed by measuring concentrations of emtricitabine and tenofovir disoproxil fumarate or their metabolites in plasma, dried blood spots, and hair. After seroconversion, genotypic and phenotypic resistance of the acquired virus was determined by standard clinical tests and by single-genome sequencing of proviral genomes. HIV partner services identified the likely transmission partner. Findings: A 21-year-old Latino man tested positive for HIV infection 13 months after PrEP initiation. He had a negative HIV antibody test, but detectable HIV RNA with 559 copies per mL. He reported good adherence to daily PrEP. He was linked to care and immediately started antiretroviral therapy, at which point his RNA was 1544 copies per mL and his HIV antibody test was positive. The HIV genotype revealed Met184Val, Leu74Val, Leu100Ile, and Lys103Asn mutations in reverse transcriptase, and the phenotype showed susceptibility to tenofovir disoproxil fumarate and resistance to emtricitabine. Segmental hair analysis of tenofovir disoproxil fumarate concentrations measured in 1 cm segments of hair from the scalp indicated consistently high adherence to PrEP in each of the 6 months before HIV diagnosis (0·0672–0·0889 ng/mg). Concentrations of tenofovir diphosphate (1012 fmol per punch) and emtricitabine triphosphate (0·266 fmol per punch) in a dried blood spot indicated high adherence over the preceding 6 weeks. Concentrations of emtricitabine (870·5 ng/mL) and tenofovir disoproxil fumarate (188·2 ng/mL) measured in plasma 3 months before HIV seroconversion confirmed adherence in the days preceding that visit. The likely transmission partner was not engaged in HIV primary care and had a similar viral genotype. Interpretation: Acquisition of HIV virus that is susceptible to tenofovir disoproxil fumarate, but resistant to emtricitabine can occur despite high adherence to PrEP. Quarterly screening for HIV and sexually transmitted diseases facilitates early diagnosis in people on PrEP; when combined with prompt linkage to care and partner services this can prevent onward transmission of HIV. Funding: US National Institutes of Health.